IoT Noise Monitoring System for Real Time Petshop Surveillance: Sistem Pemantauan Kebisingan Berbasis IoT untuk Pengawasan Toko Hewan Peliharaan Secara Real-Time - Nasrul Amin; Arief Wisaksono (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Animal welfare in petshops requires continuous monitoring to ensure that environmental conditions remain safe and comfortable for animals. Specific Background: Noise disturbances caused by animal discomfort or hunger can be difficult for petshop owners to monitor continuously, particularly when they are away from the facility. Knowledge Gap: Existing petshop monitoring practices provide limited capability for remote observation and immediate notification of excessive noise conditions. Aims: This study aimed to develop an Internet of Things based noise monitoring system that detects animal noise levels, provides visual monitoring, and delivers real time notifications to petshop owners. Results: The system integrates a NodeMCU ESP8266, GY MAX4466 sound sensor, ESP32 Cam, tilt servo, Blynk application, and Telegram notifications. Testing showed that the sound sensor detected noise optimally within a range of 1–5 m, while data transmission to the Blynk platform exhibited an average delay of 1.2 s. The camera orientation could be remotely controlled through the application, and Telegram notifications were transmitted continuously until noise levels returned to a safe category. Novelty: The proposed system combines noise detection, remote visual monitoring, camera positioning control, and automated notification services within a single IoT platform for petshop environments. Implications: The developed device provides petshop owners with real time information regarding animal conditions, supporting timely monitoring and response to noise-related situations.Highlights: Sound sensing operated reliably at distances between 1 and 5 meters. Data transmission through the mobile platform recorded an average latency of 1.2 seconds. Continuous alert messages were delivered until acoustic conditions returned to the safe category. Keywords: Internet of Things; Noise Monitoring; Petshop Surveillance; ESP32 Cam; Real Time Notification